Lidosomes: Innovative Vesicular Systems Prepared from Lidocaine Surfadrug - Martina Romeo; Elisabetta Mazzotta; Ida Daniela Perrotta; Rita Muzzalupo (MDPI AG, 2022)
Lidocaine is a local anaesthetic drug with an amphiphilic structure able to self-associate, under certain conditions, in molecular aggregates playing the role of both carrier and drug. The aim of this study was to determine the optimal conditions for obtaining vesicular carriers, called lidosomes. The new formulations were obtained using both lidocaine and lidocaine hydrochloride and different hydration medias (distilled water, acid, and basic aqueous solution). Lidosomes formulations were characterized in terms of size, ζ-potential, drug retained, stability formulation, and ex vivo permeation profile. Moreover, lidosomes were incorporated in two different gel structures: one based on carboxymethylcellulose and one based on pluronic F-127 to achieve suitable properties for a topical application. Results obtained showed that lidocaine showed a better performance to aggregate in vesicular carriers in respect to hydrochloride form. Consequently, only formulations comprised of lidocaine were studied in terms of skin permeation performance and as carriers of another model drug, capsaicin, for a potential combined therapy. Lidocaine, when in form of vesicular aggregates, acted as percutaneous permeation enhancer showing better permeation profiles with respect to drug solutions. Moreover, lidosomes created a significant drug depot into the skin from which the drug was available for a prolonged time, a suitable feature for a successful local therapy.